2015
DOI: 10.3201/eid2108.141846
|View full text |Cite
|
Sign up to set email alerts
|

Risk for Mycobacterial Disease among Patients with Rheumatoid Arthritis, Taiwan, 2001–2011

Abstract: Risk for illness and death are increased for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 32 publications
(48 reference statements)
2
40
0
Order By: Relevance
“…Rheumatoid arthritis (RA) is a well-established risk factor for TB [38]. In Taiwan, the risk of TB development was 2.28-fold higher in RA patients than in the general population [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rheumatoid arthritis (RA) is a well-established risk factor for TB [38]. In Taiwan, the risk of TB development was 2.28-fold higher in RA patients than in the general population [8].…”
Section: Introductionmentioning
confidence: 99%
“…In Taiwan, the risk of TB development was 2.28-fold higher in RA patients than in the general population [8]. Tumor necrosis factor (TNF) plays a key role in the immunity against TB [9].…”
Section: Introductionmentioning
confidence: 99%
“…Most individuals infected with M. tuberculosis have an LTBI, and this population is an important reservoir for disease reactivation (3). Increased evidence indicates an elevated TB risk in patients with rheumatoid arthritis (RA) (4,5); the risk is even higher for those receiving anti-tumor necrosis factor alpha (TNF-␣) therapy (6). Gardam et al (7) revealed that active TB in RA patients receiving anti-TNF-␣ therapy appears to be largely caused by LTBI reactivation.…”
mentioning
confidence: 99%
“…There is a high prevalence of TB in Taiwan, despite the extensive implementation of TB control measures and universal Bacillus Calmette-Guérin (BCG) vaccination [2]. An increased TB prevalence has been reported in rheumatoid arthritis (RA) patients [3], and its risk increased further in those receiving biologic therapy [46]. Guidelines have recommended that screening for latent TB infection (LTBI) should be carried out and isoniazid prophylaxis (INHP) be initiated if LTBI exists [7].…”
Section: Introductionmentioning
confidence: 99%